Acupuncture Points and Their Relationship with Multireceptive Fields of Neurons - Salvador Quiroz-González; Sergio Torres-Castillo; Rosa Estela López-Gómez; Ismael Jiménez Estrada (Medical Association of Pharmacopuncture Institute, 2017)
In Traditional Chinese Medicine, acupuncture points (APs) have been emphasized as key elements that generate the therapeutic effects of acupuncture. At the spinal cord or supraspinal level, sensory neurons located in the dorsal horn receive an extensive supply of sensory information from skin and muscle receptors through peripheral afferent nerves. The stimulated skin area that influences the activity of a spinal sensory neuron is known as the peripheral receptive field (RF) of that neuron. By considering that a particular AP location involves the activation of one or various RFs, it can be assumed that several sensory central neurons are the site of convergence of the peripheral input generated by acupuncture stimulation. However, stimulation on nonacupoint sites could also activate skin areas with RFs that have been sensitized, and they could be involved in the generation of nonspecific effects of acupuncture, as seen in clinical practice. From the latter, it is suggested that effective APs, and even nonacupoints, are associated with a particular arrangement of RFs, and their study will be useful for understanding the intrinsic mechanisms of acupuncture and for the development and identification of more efficient sites and modes of acupuncture stimulation to evoke optimal therapeutic actions.